N-[(1Z)-Cyclodec-5-yn-1-ylidene]hydroxylamine - Heiner Detert; Dieter Schollmeyer (IUCrData)
The crystal structure of cyclodecynone oxime, C10H15NO, is reported. Two twist-boat-shaped cycloalkynes are centrosymmetrically connected via oxime hydrogen bridges. Deformation of the alkyne unit results from ring strain.